Strategies for Enhancing Health Literacy Among Students Through Campus Radio Mass Communication at Polytechnic of The Ministry of Health in Padang - Widdefrita; Novelasari; Amos, John; Zakiyyah, Nurul Azma (proceedinginternational, 2024)
The success indicators of health development are 80% determined by the health human resources. The ability of health literacy in students is a crucial component because students will eventually become role models for healthy living behaviors and provide healthcare services to the community. The purpose of this research is to determine the strategy for improving students' health literacy through campus radio mass communication at the Health Polytechnic of the Ministry of Health in Padang. The research employs a quantitative approach, using questionnaires to assess the level of health literacy among students through campus radio mass communication at the Health Polytechnic of the Ministry of Health in Padang. The sample size in this study consists of 153 students from the Health Polytechnic of the Ministry of Health in Padang, selected through non-random sampling using quota sampling techniques from each department or program. The research indicates a significant relationship between the variable of health information access and health literacy among students at the Health Polytechnic of the Ministry of Health in Padang (p-value < 0.05).